2015
DOI: 10.1371/journal.pone.0145153
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Muscle-Like Cells Generated from Human Mesenchymal Stromal Cells Display Marker Gene Expression and Electrophysiological Competence Comparable to Bladder Smooth Muscle Cells

Abstract: The use of mesenchymal stromal cells (MSCs) differentiated toward a smooth muscle cell (SMC) phenotype may provide an alternative for investigators interested in regenerating urinary tract organs such as the bladder where autologous smooth muscle cells cannot be used or are unavailable. In this study we measured the effects of good manufacturing practice (GMP)-compliant expansion followed by myogenic differentiation of human MSCs on the expression of a range of contractile (from early to late) myogenic markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 67 publications
3
25
0
Order By: Relevance
“…αSMA and VMT are known as common differentiation markers of smooth muscle cells, while MYH11 and CNN1 are late differentiation markers and more specific to contractile smooth muscle cells. [ 37 ] Expression of MYH11 and CNN1 in the tissues over time (Figure 6C,D) revealed that hiSMCs were differentiated into contractile phenotype in the aligned scaffolds and cytologically capable of performing potential contraction/relaxation. We also detected the expression of type I collagen (COL1A1), as the differentiation of SMCs induces the deposition of ECM proteins including collagen.…”
Section: Resultsmentioning
confidence: 99%
“…αSMA and VMT are known as common differentiation markers of smooth muscle cells, while MYH11 and CNN1 are late differentiation markers and more specific to contractile smooth muscle cells. [ 37 ] Expression of MYH11 and CNN1 in the tissues over time (Figure 6C,D) revealed that hiSMCs were differentiated into contractile phenotype in the aligned scaffolds and cytologically capable of performing potential contraction/relaxation. We also detected the expression of type I collagen (COL1A1), as the differentiation of SMCs induces the deposition of ECM proteins including collagen.…”
Section: Resultsmentioning
confidence: 99%
“…SMCs in adult blood vessels exhibit low rate of proliferation, low synthetic activity, and expression of distinctive SMC markers such as a-SM-actin, SM-myosin, and other SMspecific markers, including calponin. 44,45 SMCs in vascular grafts exposed to stiffer matrices tend to undergo dedifferentiation, and transit into a pro-proliferative myofibroblastlike phenotype, particularly at the site of suture. 46,47 The difference in the elasticity of the native artery and the vascular graft at the site of suturing is called compliance mismatch.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that P/PL is capable of inducing a smooth muscle-like phenotype in human bmMSCs [14,15]. The goal of the present study was to measure whether human P/PL alone was also sufficient in inducing a skeletal myogenic and neurogenic phenotype.…”
Section: Introductionmentioning
confidence: 90%
“…However, the overall efficacy and clinical endpoints were largely inconsistent. Such inconsistencies could be attributed to the dosage of injected cells, number of injections, delivery route, cell survival in situ after injection, endpoints examined, or timing of followup, but could also simply be the result of how the MSCs were prepared or expanded prior to application, as we have shown that expansion conditions can impact MSC lineage determination and prime the cells towards certain phenotypes [14,15].…”
Section: Introductionmentioning
confidence: 99%